Techno-economic analysis of the thermal energy saving options for high-voltage direct current interconnectors. (1st August 2019) - Giampieri, Alessandro; Ma, Zhiwei; Ling Chin, Janie; Smallbone, Andrew; Lyons, Padraig; Khan, Imad; Hemphill, Stephen; Roskilly, Anthony Paul
Highlights: High-voltage direct current interconnectors are used for long-distance electricity transfer. They transfer 100 s GW of electrical power with around 1% losses mainly to heat. This paper compares alternative solutions for heat recovery and reutilisation. Data from the Moyle interconnector between Scotland and Northern Ireland is used. Heat-to-electricity and heat-to-cooling technologies are compared. Abstract: High-voltage direct current interconnection stations are increasingly used for long-distance electricity transport worldwide, due to efficiency and economic reasons. The identification and evaluation of cost-effective waste heat sources appropriate for recovery and reutilisation represent an opportunity that can improve the efficiency of high-voltage direct current stations, resulting in significant savings in energy consumption and reduction of the carbon footprint. The paper is the first to investigate the technological and economic feasibility of heat recovery at a major interconnector power station. Once identified the potential recoverable heat sources and evaluated the latest advancements in thermal energy recovery technology, a technological and economic analysis of two potential heat recovery strategies has been performed. While the heat-to-electricity technology was proved to be technologically but not economically feasible, the realisation of a combined liquid desiccant and evaporative cooling heat recovery strategy was proved to present the best economic performance with a payback period of about 5 years and a levelised cost of saved energy of 0.155 €/kWh, depending on the heat recovery and size of the system. Additional economic savings can be obtained for high-voltage direct current stations located in hot and humid climates, where the moisture removal ability of liquid desiccant technology could be particularly advantageous.